Experimental Analysis of a Rectangular Base Spouted Bed in Continuous Operation - Reyes-Salinas, A; Henriquez-Vargas, L; Pailahueque-Barahona, N (Italian Association of Chemical Engineering - AIDIC, 2019)
In this work, the pressure drops and characteristic velocities of a rectangular section spouted bed (RSB) used to fluidize sawdust particles which is a little used wet residue, are reported. The RSB considered was built in acrylic, with dimensions 1000 x 300 x 150 mm3 and with an air intake opening of 14 by 150 mm2. The conditions that allowed its continuous operation were sought and analyzed. In a first stage of the study, the fluid-dynamics of sawdust beds was characterized for particles with average sizes of 1.2, 1.7 and 2.4 mm, and with moisture content between 7 and 50 %, for sawdust loads of 400, 500 and 600 g. The characteristic parameters obtained experimentally were compared with predictions made with correlations from literature. In a second stage, a feeding system was installed on one of the walls of the RSB, consisting of a worm screw feeder provided with a variable velocity motor. On the opposite wall, an opening with a circular section of 5 cm in diameter was made to allow the solids to escape. In this unit, the conditions that allowed a stable operation for different feed rates and moisture content of the solids were determined, registering the bed height and the air flow rate. Stationary conditions were determined for sawdust feed rates between 18 and 45 kg/h and air velocities between 0.88 and 1.28 m/s, for the three particle sizes tested. Additionally, it was observed in experiences at room temperature (20 ºC), a decrease in the moisture content of the order of 10 % in 60-minute experiences, which exhibit the potential of the equipment to dry granular solids. Copyright © 2019, AIDIC Servizi S.r.l.